The Triple Helix after communism: Russia and China compared - Harley D. Balzer; Jon Askonas (Triple Helix, 2016)
Russia and China both are endeavoring to transform Soviet-style R&D systems characterized by separate education, research and business spheres into something more suited to a knowledge economy supporting innovation. The Triple Helix model is an attractive configuration, derived from the practices of the most successful innovation systems, and suggesting that the three key actors-universities, business, and the state-might in some instances substitute for each other. A model placing the state at the center appeals to non-democratic regimes and countries endeavoring to catch up with OECD nations.
Keywords: 330; Triple Helix; Innovation; Chinese science; Post-Soviet science; Russian science; Science policy